2012
DOI: 10.1152/ajprenal.00034.2012
|View full text |Cite
|
Sign up to set email alerts
|

Na delivery and ENaC mediate flow regulation of collecting duct endothelin-1 production

Abstract: Collecting duct (CD) endothelin-1 (ET-1) is an important autocrine inhibitor of Na and water transport. CD ET-1 production is stimulated by extracellular fluid volume expansion and tubule fluid flow, suggesting a mechanism coupling CD Na delivery and ET-1 synthesis. A mouse cortical CD cell line, mpkCCDc14, was subjected to static or flow conditions for 2 h at 2 dyn/cm(2), followed by determination of ET-1 mRNA content. Flow with 300 mosmol/l NaCl increased ET-1 mRNA to 65% above that observed under static con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 32 publications
3
33
1
Order By: Relevance
“…The flow response was dependent on intracellular and extracellular Ca 2ϩ , phospholipase C (PLC), and protein kinase C (PKC). A subsequent study (67) found that increasing perfusate NaCl concentration increased the ET-1 flow response in mpkCCDcl4 cells and that this effect was due to Na ϩ but not Cl Ϫ or osmolality. The ET-1 flow response was dependent on the epithelial Na ϩ channel (ENaC), being inhibited by amiloride or benzamil and stimulated by aldosterone.…”
Section: Regulation Of Collecting Duct Et Productionmentioning
confidence: 91%
“…The flow response was dependent on intracellular and extracellular Ca 2ϩ , phospholipase C (PLC), and protein kinase C (PKC). A subsequent study (67) found that increasing perfusate NaCl concentration increased the ET-1 flow response in mpkCCDcl4 cells and that this effect was due to Na ϩ but not Cl Ϫ or osmolality. The ET-1 flow response was dependent on the epithelial Na ϩ channel (ENaC), being inhibited by amiloride or benzamil and stimulated by aldosterone.…”
Section: Regulation Of Collecting Duct Et Productionmentioning
confidence: 91%
“…However, the effect of extracellular NaCl or osmolality on CD ET-1 production is controversial, with conflicting findings being reported (27). Recent studies by our group have suggested that tubule fluid flow may be involved: exposure of mpkCCD cells, a cortical CD cell line, to shear stress increased ET-1 mRNA (28,36). Interestingly, this flow augmentation of mpkCCD ET-1 mRNA content was due to Na ϩ delivery; increasing Na ϩ delivery increased epithelial Na ϩ channel (ENaC)-mediated Na ϩ entry, which led to enhanced mitochondrial Na ϩ /Ca 2ϩ exchange (NCLX), increased intracellular Ca 2ϩ concentration ([Ca 2ϩ ] i ), activation of Ca 2ϩ signaling pathways, and, ultimately, increased ET-1 gene transcription (36).…”
mentioning
confidence: 99%
“…However, this effect quickly reverses and would most likely dissipate by the time the kidney is removed to the time that whole cell recordings are made. A recent paper suggests that endothelin-1 (ET-1) production in the CCD is directly correlated with Na ϩ delivery and tubular flow rate (30). As ET-1 has been shown to be a potent inhibitor of ENaC activity (5,32), it is another potential regulator of I Na during acute sodium loading.…”
Section: Discussionmentioning
confidence: 99%